Small business management entrepreneurship and beyond - Hatten, Timothy S. (Cengage Learning, 2016)
Small Business Management provides a balanced introduction to both entrepreneurship and small business management, with a focus on achieving and maintaining a sustainable competitive advantage as a small organization. Current issues, including global opportunities, service, quality and technology, are highlighted throughout the text.